AB0535 Effects of tocilizumab on bone density and metabolism in patients with active rheumatoid arthritis. (23rd January 2014) - Pierguidi, S.; Bertoldi, I.; Adinolfi, A.; Filippou, G.; Picerno, V.; Galeazzi, M.; Frediani, B.
Abstract : Background: juxta-articularosteoporosis, erosionsand systemic osteoporosis are the three main radiological features in patients affected by rheumatoid arthritis. A series of studies have emphasized the close relationship between disease activity and bone loss, suggesting a common pathogenetic mechanism regardinosteoporosis and joints erosion. Tocilizumab is a interleukin-6 receptor-inhibiting monoclonal antibody, able to bind with high affinity to both soluble form and membrane receptor. Currently there are no data regarding the efficacy of tocilizumab on fracture risk and bone mass. Objectives: The aim of our study was to evaluate the changes in BMD and some markers of bone metabolism in patients with active rheumatoid arthritis treated with tocilizumab. Methods: All patients referred to our outpatent clinic fromNovember 2010to November2011 affected with rheumatoid arthritis, according to ACR 1987 criteria and eligible to receive tocilizumab infusion were enrolled to the study.Patients underwent infusion therapy with tocilizumab, 8 mg/kg, monthly and performed a bone densitometry at baseline and after 1 year of therapy. ESR, CRP, IL6, crosslaps and a whole series of bone metabolism markers (OPG, RANKL, DKK1) were evaluated at baseline, after six months and at 1 year after beginning of the therapy. The following pìvariables were assessed and recorded: sex, age, disease duration, previous or contemprorary use of DMARDs steroids. Results: 18 patients were enrolled, but of these 6 patients discontinued therapy in the first year of treatment, 3 patients due for ineffectiveness and 3 because of infectious complications. The data of 12 patients were used for the statistic analysis. One patient was osteoporotic, 9 osteopenic and 2 had a normal bone mineralization. All patients had failed at least one anti-TNF alpha. After one year of treatment a significant increase in bone mineral density at L1-L4 (p=0.02) was detected. An increase, although not significant was also highlighted for the BMD of the total femour, with no variation in total body BMD and femoral neck. The ESR and CRP decreased at 6 months and remained low at 1 year. No statistically significant change was observed for serum IL-6, serum crosslaps, OPG, DKK1, RANKL during the observation period; there was a downward trend for the Serum Cross Laps, IL6 and DKK1. There was a negative statistically significant correlation between the BMD of the lumbar spine and IL6 (-0.70, p=0.04) and between BMD of the lumbar spine and serum Cross Laps (-0.59, p=0.05). There was a positive non significant correlation between the total and neck femur with osteoprotegerin (0.45). There was a negative non significant correlation between ESR and CRP (decreased) and bone mineral density, osteoprotegerin/RANKL, DKK1 (increased). Conclusions: Our work shows that Tocilizumab has a protective effect on bone, resulting in reduced bone resorption process and increased bone formation. More studies are needed to confirm our preliminary data References: C. J. Edwards and E. Williams. The role of interleukin-6 in rheumatoid arthrtitis-assiociated osteoporosis. Osteoporos Int (2010); 21: 1287-93 K. Katsuaki, N. Atsushi, I. Yasuo and H. Kaori. Osteoprotegerin expression in bone marrow by treatment with tocilizumab in rheumatoid arthrtitis. Rheumatolo Int 2011 Jul 26 Disclosure of Interest: None Declared